An Analysis of Specialty-Specific Microsurgical Head and Neck Reconstruction: A Look at a Single Institution and National Trends Over a Decade. Issue 4 (April 2020) - Kozak, Geoffrey M.; Katzel, Evan B.; Rose, Jessica F.; Nathan, Shelby L.; Wu, Liza C.
Abstract : Introduction: Head and neck free flap (HNFF) reconstructions have historically utilized a multidisciplinary approach between otolaryngology head and neck surgery (OHNS) and plastic surgery (PS). However, there seems to be a trend toward both the extirpative and reconstructive portions being performed by OHNS. We aimed to elucidate the volume trend in HNFF reconstruction over the last decade. Methods: Data were collected by 3 modalities: electronic medical record search of patients who underwent HNFF surgery at our institution (2013–2018), survey data from microsurgery fellowship programs (2007–2017), and National Surgical Quality Improvement Program (NSQIP) query of cases receiving designated HNFF Current Procedural Terminology codes (2011–2016). Data were analyzed with trends in HNFF reconstruction as our primary outcome. Results: At our institution, HNFF reconstructions increased 4-fold (59–227). Percentage of cases by PS decreased from 18.6% to 6.0%, whereas that of OHNS increased 81.4% to 94.0% ( P = 0.009). Survey data, completed by microsurgery fellowship program directors (23/81 [27.2%]), revealed the number of OHNS programs in 2007 performing 100 or more HNFF cases compared with PS was 40% (6/15) to 12.5% (1/8) ( P = 0.172). By 2016, that number increased significantly for OHNS to 73.3% (11/15), whereas that of PS remained stagnant at 12.5% (1/8) ( P = 0.005). According to NSQIP data, the percentage of cases performed by PS in 2011 was 52%, which was greater than OHNS's share of 43%. The other 5% was allotted to either orthopedic, oral and maxillofacial surgery, or general surgery. In 2013, those numbers reached a peak for PS at 55% and a nadir for OHNS at 36%. However, by 2016, the percentage of HNFF cases reversed. where 58% of cases were performed by OHNS and only 38% by PS. When comparing the 2011 data to the 2016 data, OHNS had a 134% increase, whereas PS had a 27% decrease ( P = 0.003). Conclusions: Head and neck free flap reconstruction has grown dramatically over the last 10 years. Plastic surgeons are performing fewer cases, whereas otolaryngology head and neck surgeons perform more as indicated by institutional, microsurgery fellowship program director survey, and NSQIP data.